Collagen bio stimulators in orofacial Harmonization: A narrative review of the literature (Research, Society and Development, 2025)
One of the areas that has stood out the most is orofacial harmonization, which seeks to balance the proportions of the face and promote a more youthful appearance. To combat the effects of time and restore youth, harmonization offers a variety of treatments, including collagen biostimulators. These substances stimulate the natural production of collagen, promoting a lifting effect and improving skin quality. Among the main collagen biostimulators used, the following stand out: calcium hydroxyapatite (CaHA), poly-L-lactic acid (PLLA), polycaprolactone (PCL), platelet-rich plasma (PRP) and fibrin-rich plasma (PRF) and polydioxanone threads (PDO). The objective of this research is to conceptualize and present the main biostimulators found in the aesthetic market for orofacial harmonization. In conclusion, it was possible to observe that there is a wide variety of collagen biostimulators on the market, with different forms of application, cost, techniques and with different treatment objectives. The professional must be qualified and have mastery of the procedures he will perform, because even though it is a procedure considered safe, its adverse effects are mainly linked to poor placement of the product. In addition, collagen biostimulation focuses on preventing aging, which results not only in resolving the patient's complaint, but also brings an improvement in the patient's facial health.